Impact Damage Analysis of Fiber Reinforced Plastic Structure with Rib. (30th March 2022) - Linghua, Xiong; Zhimao, Ming; Kelun, Zhao; Fan, Wang
Abstract : Fiber reinforced plastic (FRP) is a widely used structural form in engineering. FRP ribs can absorb most of the impact energy to protect the structure from damage. The purpose of this study is to obtain the impact resistance of FRP ribs by test and simulation. Taking glass fiber reinforced plastic (GFRP) oil sump as the object, the damage degree of structure under different impact angles, impact velocity, and impactor masses is compared and analyzed by material test, impact test, and simulation. It can be seen from the test results that the design of surface ribs has a great influence on the energy absorption effect of the shell. The constitutive parameters of the shell material are obtained by testing, and the failure mode of the ribs is analyzed by finite element simulation. The impact effects of flying stones with different incident angles, velocities, kinetic energy, and geometric dimensions on the shell are compared and analyzed. The results show that, at the same impact energy, the impact resistance characteristics change regularly under different working conditions. Under a certain incident angle, the damage effect caused by flying stones in a specific mass range is greater. Beyond a certain incident angle, the damage begins to occur, and the larger the incident angle is, the greater the damage effect is. Combined with the actual situation and road standards, the defense of medium quality flying stones is a major concern in the design of oil pan. The results are helpful for designing reasonable ribs to improve the reliability of FRP structures.